Identification of parameters of mathematical models of nonlinear components of electrical complexes and systems in their deep interaction - V. Z. Kovalev; A. G. Scherbakov; O. V. Arkhipova; S. V. Langraf; D. S. Bunkov; S. S. Esin (Омский научный вестник)
The article offers a method for identifying parameters of mathematical models of electrical complexes and systems. The method is designed to create a system for monitoring the influence of nonlinear components of electrical complexes and systems in their deep interaction on the quality of electrical energy in the load node. The application of the coefficient of variation of parameters as a criterion for evaluating the reliability of identification of parameters of mathematical models is justified. As the initial information, digitized data of the voltage at the point of common connection and the currents of individual components of the analyzed complex are used. The mathematical apparatus of identification is based on a modification of the Marquardt method. A series of computational experiments confirms the main theoretical provisions of the article. It is shown that it is possible to identify the parameters of models of complex components with a significantly nonlinear form of stress at the point of common connection.